Espumas poliméricas contendo resíduo de catalisador da indústria de petróleo como adsorventes para contaminantes orgânicos aquosos - Marys Lene Braga Almeida (2017)
The petroleum cracking catalyst residue (RC) was characterized and chemically modified with 3-aminopropyltriethoxysilane in order to be applied as an unconventional adsorbent material in leaked oil and hydrocarbons containment in the sea, and sunflower oil was used in the study. RC showed a high specific superficial area (150±15 m2/g) and a potential use as an adsorbent. To investigate ways of mitigating the contamination of water with pesticides, natural resource-based polyurethane foams (PUF) containing different amounts of RC were tested as adsorbents in aqueous solutions with chlorobenzene and the pesticides atrazine (ATZ) and trifluralin (TFL), both responsible for negative impacts on the environment and on human health. The adsorbents were characterized by thermogravimetric analysis, scanning electron microscopy, energydispersive X-ray spectroscopy, X-ray microtomography, infrared spectroscopy, X-ray diffraction and contact angle. PUF and RC surface charges were evaluated by their zeta potential. ATZ adsorption was investigated as a function of the foam composition, initial contaminant concentration, solution pH, polyurethane preparation method and time of contact. ATZ kinetics results were fitted in the pseudofirst-order model and the equilibrium process was well adjusted by the Freundlich isotherm model. The results showed that the adsorbents porosity, pore size and pore interconnectivity were adequate for the contaminants removal. At pH 2, foams with high RC content obtained higher efficiency rates of ATZ removal (25%) compared to PUF (12%). On the other hand, ATZ removal was disfavored at a high pH, which was attributed to restricted ATZ interactions due to changes in the adsorbent surface charge. ATZ desorption was more effective at a high pH, allowing the regeneration and reuse of the adsorbents. The presence of other species, such as pectin, did not interfere with the removal of atrazine and, therefore, the proposed method also suggested to be adequate in the removal of the contaminant in food. The composite with a high amount of RC incorporated in the foam (PUF80) presented high removal efficiency (39%) of trifluralin in aqueous solutions with low pHs and the desorption was enhanced at higher pHs